2014
DOI: 10.2147/cia.s63504
|View full text |Cite
|
Sign up to set email alerts
|

The merits and problems of Neuropsychiatric Inventory as an assessment tool in people with dementia and other neurological disorders

Abstract: ObjectiveThe Neuropsychiatric Inventory (NPI) is one of the most commonly used assessment scales for assessing symptoms in people with dementia and other neurological disorders. This paper analyzes its conceptual framework, measurement mode, psychometric properties, and merits and problems.MethodAll articles discussing the psychometric properties and factor structure of the NPI were searched for in Medline via Ovid. The abstracts of these papers were read to determine their relevance to the purpose of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 52 publications
2
79
0
3
Order By: Relevance
“…Chapman and colleagues (2004) examined the effects of cognitive communication stimulation for people with dementia. This study, however, measured carers' distress by using the Neuropsychiatric Inventory (Cummings et al, 1994), which is not a validated measure for carer distress (Lai, 2014). The study by Spector et al (2001) described the development and implementation of group CS therapy for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Chapman and colleagues (2004) examined the effects of cognitive communication stimulation for people with dementia. This study, however, measured carers' distress by using the Neuropsychiatric Inventory (Cummings et al, 1994), which is not a validated measure for carer distress (Lai, 2014). The study by Spector et al (2001) described the development and implementation of group CS therapy for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…390 This holds for npiq where the test set mean is poorly estimated (∆ cv < 0). This can be explained by the fact that this score does not yield a very sensitive characterization of dementia, nor does it differentiate between clinical groups (Lai, 2014). Also, the clinical dementia rate (CDR) has only 5 possible values, 395 which makes regression approaches less accurate.…”
mentioning
confidence: 99%
“…As mentioned previously, the existing reviews [8,13,22,11,23] focused only on the reported psychometric properties of the NPI, and have not addressed whether these data are sufficient in light of general psychometric recommendations. To address this gap, we used a comprehensive framework for the evaluation of psychometric properties in development and validation studies of the NPI.…”
Section: Review Proceduresmentioning
confidence: 99%
“…The NPI is a flexible and a relatively brief informant questionnaire that screens for the most common NPS in AD and other memory disorders. It has been utilized both clinically and in research, with applications in clinical trials, neuroimaging, descriptive psychopathology, and as a validity benchmark for the development of subsequent NPS scales [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation